Penggunaan Model Inside Outside Circle terhadap Hasil Belajar Sejarah Indonesia Pada Materi Kerajaan Sriwijaya - Yuly - Agustina; Isbandiyah I; Agus Susilo (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
This is study aims to determine the use of the Inside Outside Circle model of the learning outcomes of Indonesian history in Sriwijaya kingdom material. The research method used is a quantitative method, with a pure experimental approach. The designed of this study is Pretest-Posttest Control Group Design. The type of research instrument used was a multiple choice test consisting of 35 questions. Technique for analyzing the data used quantitative techniques. The population in this study were all X grade students in academic year 2018/2019. And sample of the data taken in X grade students at AKL 1 as the experimental and X OTP 2 as the control. The experimental class was treated using the Inside Outside Circle model on the Sriwijaya Kingdom learning material and the control class was not treated inside the circle learning model. Based on the analysis of the use of research hypotheses, the results of this study conclude there is an influence of the Inside Outside Circle learning model on the learning outcomes of Indonesian history on Sriwijaya kingdom material.